РЕНТГЕНОВСКОЕ ИЗЛУЧЕНИЕ ГАЛАКТИК БЕЗ АКТИВНЫХ ЯДЕР - Тугай A. B.; Василенко, А. А. (Одеські астрономічні публікації, 2011)
We perfirmed cross-correlation of SDSS galaxies and X-ray sources from 2XMMi catalogue. We selected galaxies with strong NII[6583] and OIII[5007] lines to divide them to starburst galaxies and AGNs. In result we obtained samples of 148 candidates to starburst galaxies and 138 AGNs. We built X-ray spectra for starburst galaxies I Zw 49, NGC4303, NGC4490 and NGC5907 and approximated them by powerlaw model with indexes 2.6, 2.8, 2.1 and 1.6 correspondingly. We also found that NGC4254 has thermal spectum with kT=0.2 keV. For NGC4254 and NGC4303 we obtained spectrum of galaxy disc without nuclear region.